Cerebral oligodendroglioma mimicking intraventricular neoplasia in three dogs. (May 2015) - Rissi, Daniel R.; Levine, Jonathan M.; Eden, Kristin B.; Watson, Victoria E.; Griffin, John F.; Edwards, John F.; Porter, Brian F.
Oligodendroglioma is one of the most common primary central nervous system neoplasms of dogs. It is often diagnosed in older, brachycephalic breeds, and although its typical clinical features and neuroanatomic location have been well described, less common presentations may hinder its diagnosis. We describe 3 cases of canine cerebral oligodendroglioma that clinically and grossly present as intraventricular tumors. Histologic findings in all cases were typical of oligodendroglioma. Neoplastic cells were uniformly immunoreactive for Olig2 and negative for neuron-specific enolase, neurofilament, and glial fibrillary acidic protein. In addition to the immunopositivity for Olig2, a cluster of morphologically distinct neoplastic cells in one of the cases was immunoreactive for synaptophysin, and the case was diagnosed as an oligodendroglioma with neurocytic differentiation. Based on these findings, oligodendroglioma should be included as a differential diagnosis for intraventricular neoplasia in dogs. Furthermore, oligodendroglioma with ventricular involvement should be differentiated from central neurocytoma by immunohistochemistry.